2009
DOI: 10.1139/h09-067
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eccentric treadmill exercise on inflammatory gene expression in human skeletal muscle

Abstract: The present study examined the skeletal muscle expression of several genes related to the inflammatory process before and after a bout of downhill running. Twenty-nine males between the ages of 18 and 35 years performed a 45-min downhill (-17.5%) treadmill protocol at 60% of maximal oxygen consumption. Venous bloods samples and muscle biopsy samples from the vastus lateralis were donated prior to and at 3-h and 24-h postexercise, along with ratings of perceived muscle soreness. Serum creatine kinase (CK) was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 42 publications
3
36
1
Order By: Relevance
“…Recently, it has been suggested that IL-6 acts as an energy sensor, exhibiting local and endocrine metabolic effects (278,279). IL-6 and other cytokines such as IL-8, cyclooxygenase2, and TNF-a are significantly activated after unaccustomed muscle contractions, which cause microdamage to sarcomeres (54,208). The repair of the damage by satellite cells is crucial, as these cells divide and fuse to form myotubes.…”
Section: Exercise-induced Inflammation and Rosmentioning
confidence: 99%
“…Recently, it has been suggested that IL-6 acts as an energy sensor, exhibiting local and endocrine metabolic effects (278,279). IL-6 and other cytokines such as IL-8, cyclooxygenase2, and TNF-a are significantly activated after unaccustomed muscle contractions, which cause microdamage to sarcomeres (54,208). The repair of the damage by satellite cells is crucial, as these cells divide and fuse to form myotubes.…”
Section: Exercise-induced Inflammation and Rosmentioning
confidence: 99%
“…Indeed, they demonstrated that exercise-deprivation induced a cluster of physiological abnormalities, similar to metabolic syndrome (such as insulin resistance, impaired glucose uptake and hyperlipidemia). Moreover, exercise also significantly alters muscle gene expression [130]. Thus, it has been proposed that active muscle might secrete one or more factors such as myokines that mediate important changes in gene expression.…”
Section: Physical Exercisementioning
confidence: 99%
“…One of such factors could be IL-6, despite its well known role in the pro-inflammatory pathways. Muscle contraction directly stimulates release of IL-6, which in turn stimulates sequential release of IL-1ra and IL-10, and trained muscle (i.e., muscle with low glycogen content) releases more IL-6 than untrained muscle [130,131]. Although IL-6 mediates some of the physiological effects of exercise, other factors are likely to play a role in this process, such as TNF-, IL-18 and/or brain-derived neurotrophic factors, thus suggesting that skeletal muscle and specifically physical exercise could be considered as mediators to counteract inflamm-ageing at systemic level [132].…”
Section: Physical Exercisementioning
confidence: 99%
“…Researchers use eccentric exercise as a model for acute inflammation with an assumption that blood flow increases right away as it would in acute injury. 15,16 However, the extent at which blood flow increases, if at all, is unknown.…”
mentioning
confidence: 99%